Using Belimbing Wuluh (Averhoa blimbi L.) As A Functional Food Processing Product - Ranggi Rahimul Insan; Anni Faridah; Asmar Yulastri; Rahmi Holinesti (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
The rapid development of science, technology, and lifestyle patterns at this time makes the desire of consumers for processed food products not only limited as a source of nutrition but also must be able to provide benefits for health. It coined the term called functional food. Functional foods are foods that contain active components and are used for the prevention or cure of diseases to achieve optimal health. Starfruit Wuluh contains active components / pharmaceutic compounds that are buffer, antibacterial and antioxidant in the roots, stems, leaves, and fruits that are very useful for health. Functional foods made from raw materials of Belimbing Wuluh based on several studies have produced several products both in the form of food and beverages such as; dried sweets, jams, syrups, jelly drinks, candy, dates, and lime. The purpose of this paper is to find out what processed food products can be used as food or drinks from Belimbing Wuluh without reducing the typical flavor of Starfruit. It also provides information that this fruit is not only used as a food spice but also functions as a more commercial food product with high selling value.